Strategic alliances between banks and fintechs for digital innovation: Motives to collaborate and types of interaction - Milan F. Klus; Todor S. Lohwasser; Friedrich Holotiuk; Jürgen Moormann (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2018)
In times of digitalization, firms increasingly need to form alliances due to the higher complexity and greater dynamics of markets. Digital innovation poses challenges for established institutions (e.g., banks) in adapting to changing rules that are set by new competitors and higher customer expectations. However, young firms providing technical solutions for the financial services industry (fintechs) also face difficulties, such as meeting regulatory requirements. Due to the shortcomings of both banks and fintechs, firms in the financial services industry are increasingly forming alliances. We conducted interviews to examine the motivations of both banks and fintechs to join forces. The resulting motives are categorized as matching, complementary, and neutral. The alliances in our sample can be differentiated into financial investments and customer-service provider relationships, with the second category being most common. However, our findings reveal that the occurrence of particular motives is not linked to certain types of alliances. Building on these findings, we develop a motivation framework and derive practical implications. – – In Zeiten der Digitalisierung steigt die Notwendigkeit von Unternehmensallianzen aufgrund steigender Komplexität und Dynamik. Digitale Innovationen führen dazu, dass etablierte Unternehmen sich veränderten Rahmenbedingungen anpassen müssen, die von neuen Wettbewerbern und steigenden Kundenerwartungen ausgehen. Aber auch junge Unternehmen, die technische Lösungen für die Finanzdienstleistungsbranche anbieten (Fintechs), haben Schwierigkeiten, etwa bei der Erfüllung hoher regulatorischer Anforderungen. Diese Defizite auf beiden Seiten führen dazu, dass eine zunehmende Anzahl von Allianzen in der Finanzdienstleistungsbranche zu beobachten ist. Wir haben Interviews durchgeführt, um die dahinterliegenden Beweggründe von Banken und Fintechs zu untersuchen. Die Motive wurden anhand der Häufigkeit ihrer Nennung sowie nach ihrem Übereinstimmungsgrad kategorisiert. Die Allianzen in unserer Stichprobe können in Finanzinvestitionen und Kunde-Dienstleister-Beziehungen unterschieden werden, wobei die zweite Kategorie am häufigsten zu finden ist. Unsere Ergebnisse zeigen jedoch, dass das Auftreten bestimmter Motive nicht zwangsläufig mit bestimmten Arten der Zusammenarbeit verbunden ist. Aufbauend auf diesen Erkenntnissen systematisieren wir die Motive und leiten praktische Implikationen ab.
Keywords: G21; G23; G34; L14; L24; M13; 650